2016
DOI: 10.1111/iji.12265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular comparison of Slc11a1 and Slc11a2 genes of swamp‐ and riverine‐type water buffaloes

Abstract: Solute-linked carrier 11a and 11a2 (Slc) have been associated with disease resistance and/or susceptibility across animal species. These genes have an important mechanism in the regulation against intracellular infection. This study analysed the genetic characteristic of Slc 11a and 11a2 in swamp-type and riverine-type water buffaloes to understand their immunological distinction. Characterization of Slc11a1 and Slc11a2 genes from swamp- and riverine-type water buffaloes was carried out by molecular cloning, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
0
2
1
Order By: Relevance
“…concluded that SLC5A5 is a direct target gene of the p53 signaling pathway and suggested that the DNA‐damaging agents‐mediated SLC5A5 could hypothetically potentiate its upregulation in vivo . Solute‐linked carrier has been linked to disease resistance and susceptibility in animals, with research proposing its potential as an essential mechanism in the mediation against intracellular infection . Those findings were largely inconsistent with the findings of the current study, whereby these five genes were all markedly elevated in AR, and displayed sustained high levels following allergen challenge.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…concluded that SLC5A5 is a direct target gene of the p53 signaling pathway and suggested that the DNA‐damaging agents‐mediated SLC5A5 could hypothetically potentiate its upregulation in vivo . Solute‐linked carrier has been linked to disease resistance and susceptibility in animals, with research proposing its potential as an essential mechanism in the mediation against intracellular infection . Those findings were largely inconsistent with the findings of the current study, whereby these five genes were all markedly elevated in AR, and displayed sustained high levels following allergen challenge.…”
Section: Discussioncontrasting
confidence: 99%
“…Solute-linked carrier has been linked to disease resistance and susceptibility in animals, with research proposing its potential as an essential mechanism in the mediation against intracellular infection. 32 Those findings were largely inconsistent with the findings of the current study, whereby these five genes were all markedly elevated in AR, and displayed sustained high levels following allergen challenge. AA metabolism has been shown to trigger a large release of a number of inflammatory regulators, including leukotrienes and prostaglandins, which may be involved in numerous inflammatory-associated diseases, such as asthma, rheumatoid arthritis, as well as various types of cancers.…”
Section: (A) (B)contrasting
confidence: 92%
“…SLC5A5 є прямим геном-мішенню сигнального шляху p53, опосередкований агентами, що пошкоджують ДНК [26,27]. Він пов'язаний із стійкістю до хвороб та має потенціал важливого механізму посередництва проти внутрішньоклітинної інфекції [28].…”
Section: Asthma and Allergy • 3 • 2023unclassified